Genomic Analysis of the Evolution of Phototrophy among Haloalkaliphilic Rhodobacterales - Kopejtka, Karel; Tomasch, Jürgen; Zeng, Yonghui; Tichý, Martin; Sorokin, Dimitry Y; Koblížek, Michal (Genome biology and evolution, 2017)
A characteristic feature of the order Rhodobacterales is the presence of a large number of photoautotrophic and photoheterotrophic species containing bacteriochlorophyll. Interestingly, these phototrophic species are phylogenetically mixed with chemotrophs. To better understand the origin of such variability, we sequenced the genomes of three closely related haloalkaliphilic species, differing in their phototrophic capacity and oxygen preference: the photoheterotrophic and facultatively anaerobic bacterium Rhodobaca barguzinensis, aerobic photoheterotroph Roseinatronobacter thiooxidans, and aerobic heterotrophic bacterium Natronohydrobacter thiooxidans. These three haloalcaliphilic species are phylogenetically related and share many common characteristics with the Rhodobacter species, forming together the Rhodobacter-Rhodobaca (RR) group. A comparative genomic analysis showed close homology of photosynthetic proteins and similarity in photosynthesis gene organization among the investigated phototrophic RR species. On the other hand, Rhodobaca barguzinensis and Roseinatronobacter thiooxidans lack an inorganic carbon fixation pathway and outer light-harvesting genes. This documents the reduction of their photosynthetic machinery towards a mostly photoheterotrophic lifestyle. Moreover, both phototrophic species contain 5-aminolevulinate synthase (encoded by the hemA gene) incorporated into their photosynthesis gene clusters, which seems to be a common feature of all aerobic anoxygenic phototrophic Alphaproteobacteria. Interestingly, the chrR-rpoE (sigma24) operon, which is part of singlet oxygen defense in phototrophic species, was found in the heterotrophic strain Natronohydrobacter thiooxidans. This suggests that this organism evolved from a photoheterotrophic ancestor through the loss of its photosynthesis genes. The overall evolution of phototrophy among the haloalkaliphilic members of the RR group is discussed.
Keywords: horizontal gene transfer; Bacterial Proteins; fotosyntéza; fylogeneze; Photosynthesis; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; molekulární evoluce; Evolution, Molecular; Rhodobacter; Genomics; světlo; fototrofní procesy; Aerobiosis; Phototrophic Processes; bakteriální proteiny; Anoxygenic photosynthesis; Rhodobacteraceae; photosynthesis gene cluster; bacteriochlorophyll; aerobióza; Light; genomika